Resource constraints and East European foreign trade structures - Jan Winiecki (Intereconomics, 1983)
Among the many contraints facing all participants in the international division of labour in the present decade, some seem to affect centrally planned economies (CPEs) to a greater extent than other countries. The CPEs' additional problems are due, according to Prof. Winiecki, to specific, economic system-related features, in particular their relatively high resource intensity.
Keywords: 330; Trade Policy